The anabolic effects of recombinant human growth hormone and glutamine on parenterally fed, short bowel rats - Gu, Yan (World J Gastroenterol, 2002)
AIM: To evaluate the metabolic effects associated with administration of rhGH and/or Gln in parenterally fed, short-bowel rats. METHODS: Forty SD rats subjected to 75% intestinal resection and maintained with parenteral nutrition were randomly divided into 4 groups as follows: -rhGH, -Gln; -rhGH, +Gln; +rhGH, -Gln; +rhGH, +Gln. Body weight and nitrogen balance were evaluated daily. After 6 d of PN, rats were killed, various organs were dissected and weighted, the carcasses were used for analysis of body composition. Serum GH and IGF-1 were determined by RIA method. RESULTS: Weight loss in rats with rhGH (17.4 ± 12.8 g) and rhGH+Gln (23.8 ± 3.5 g) was significantly less than rats with PN alone (29.6 ± 6.9 g) and rats with Gln-supplemented PN (31.85 ± 12.8 g), P < 0.05. The accumulated NB in rats with rhGH (1252.9 ± 294.3 mg N/d) and rhGH+Gln (1261.7 ± 85.5 mg N/d) was significantly greater than those with PN alone (704.8 ± 379.0 mg N/d) and with Gln-supplemented PN (856.7 ± 284.4 mg N/d), P < 0.05. The absolute weight of gastrocnemius muscle in rats with rhGH (2683.9 ± 341.6 mg) and rhGH+Gln (2579.1 ± 359.5 mg) was greater than those with PN alone (2176.3 ± 167.1 mg) and with Gln-supplemented PN (2141.9 ± 353.6 mg). Although the absolute weight of remnant small intestine itself was not significantly different in 4 experimental groups, the weight/length of the segments was greater in rats with rhGH and/or Gln (48.7 ± 5.5, 52.7 ± 4.1 and 67.4 ± 5.3 respectively) than those with PN alone (47.8 ± 5.0), there were synergistic effects between rhGH and Gln in improvement of the weight/length of remnant small intestine, P < 0.05. Analyses of body carcass composition showed that a higher percentage of carcass weight as protein and a lower percentage of carcass weight as fat were occurred in rats with rhGH (20.8 ± 4.0, 6.0 ± 2.6) and rhGH+Gln (21.3 ± 2.4, 4.4 ± 1.5) than those with PN alone (16.4 ± 2.4, 9.2 ± 3.7) and with Gln-supplemented PN (17.8 ± 3.0, 6.3 ± 2.0), rhGH had significant effects on alteration of body composition, P < 0.05. Serum GH and IGF-1 concentration in rats with rhGH (5.221 ± 0.8 and 425.1 ± 19.2 ng/mL respectively) and rhGH+Gln (5.507 ± 1.0 and 461.1 ± 49.9 ng/mL respectively) were greater than those with PN alone (3.327 ± 1.7 and 325.8 ± 29.6 ng/mL respectively) and with Gln-supplemented PN (3.433 ± 0.1 and 347.7 ± 55.7 ng/mL respectively), P < 0.01. CONCLUSION: rhGH significantly improves the anabolism in parenterally fed. Short bowel rats, anabolic effect with Gln is less dramatic, there is no synergistic effect between rhGH and Gln in improvement of whole body anabolism. IGF-1 plays an important part in growth-promoting effects of rhGH.